Factors associated with late-stage diagnosis of breast cancer among Egyptian women - Horeya M. Ismail; Samiha Mokhtar; Hazem El-Mansy (SAGE Publishing, 2022)
Background: Detecting Breast Cancer (BC) at earlier stages comes with a better prognosis, while diagnosis at late stages has poor outcomes and escalating mortality rates from the disease. The study aims to understand the factors associated with the latestage diagnosis of BC in Egypt. Design and Methods: A sample of 400 women with a pathologically confirmed BC were enrolled from one of the main tertiary cancer hospitals in Egypt. A cross-sectional study design was conducted. The collected data included: clinical characteristics of the tumor, socio-demographic characteristics of the studied women, reproductive and medical history, screening practices, and the time from symptom onset to definite diagnosis as suspected predictors to the stage of BC at diagnosis. Data was analyzed by crude odds ratios (95% confidence interval) and multivariate logistic regression analysis. Results: The study revealed that 47.5% were diagnosed at late stages (40% at stage III/ 7.5% at stage IV), while (52.5%) were diagnosed at early stages (6.5% at stage I/46% at stage II). A binary logistic regression model showed that unmarried females (p=0.012), had non-luminal molecular subtype of BC including HER2 enriched and triple-negative tumors (p<0.001), presentation with breast changes and a non-palpable lump (p=0.024) or nonbreast symptoms (P=0.002), a delay longer than 3 months to the first presentation by patients (p<0.001), and a delay to definite diagnosis longer than 1 month by providers (p<0.001) were significant risk factors of late-stage diagnosis of BC. Conclusions: Late-stage diagnosis of BC in Egypt is associated with the aggressiveness of some molecular subtypes and other important modifiable factors that should be addressed.